Of Couch Potatoes and Lexicographers: The Eternal Struggle Between Usage and the Imposed Neologism, and its Application to Legal Neology - Naccarato, Mario (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2009)
The author sets out to determine the sources from which legal neologisms are born and whether one source prevails over the other in regards to its prescriptive nature if any. Law's traditional sources are creators of neologisms, and each source plays a role of usage with respect to the other, whereby it can stifle or consecrate a neologism.